2008
DOI: 10.1210/me.2007-0241
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor Receptor-1 Signaling in Pancreatic Islet β-Cells Is Modulated by the Extracellular Matrix

Abstract: Maintenance of pancreatic beta-cell mass depends on extracellular stimuli that promote survival and proliferation. In the islet, these stimuli come from the beta-cell microenvironment and include extracellular matrix deposited by associated vascular endothelial cells. Fibroblast growth factor receptor-1 (FGFR1) has recently been implicated as a signaling pathway that is important for normal beta-cell function. We would like to understand how extracellular matrix and FGFR1 signaling interact to promote beta-cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 35 publications
3
46
0
Order By: Relevance
“…The islets of these mice contained a diminished number of beta-cells with reduced glucose sensitivity and impaired insulin processing, demonstrating the importance of FGF signaling in maintenance of beta-cell physiology and glucose homeostasis. We previously confirmed FGFR1 activity in adult murine pancreatic beta-cells, and we further showed changes in islet glucose-stimulated metabolism and insulin secretion in the presence of the FGFR1-ligand FGF21 (2,22). Overall, these data suggest that FGFR1-induced signaling regulates beta-cell biology via classical intracellular signaling responses and may be associated with the onset and progression of metabolic disorders such as diabetes.…”
supporting
confidence: 71%
See 3 more Smart Citations
“…The islets of these mice contained a diminished number of beta-cells with reduced glucose sensitivity and impaired insulin processing, demonstrating the importance of FGF signaling in maintenance of beta-cell physiology and glucose homeostasis. We previously confirmed FGFR1 activity in adult murine pancreatic beta-cells, and we further showed changes in islet glucose-stimulated metabolism and insulin secretion in the presence of the FGFR1-ligand FGF21 (2,22). Overall, these data suggest that FGFR1-induced signaling regulates beta-cell biology via classical intracellular signaling responses and may be associated with the onset and progression of metabolic disorders such as diabetes.…”
supporting
confidence: 71%
“…Pancreatic islets were isolated from 8-to 12-week-old C57BL6 male mice by collagenase digestion (Roche Applied Science) (22). Islets were equilibrated in full RPMI 1640 medium supplemented with 11 mM glucose, 10% FBS, and 5 units/ml penicillin/streptomycin prior to mRNA harvest or dispersion to single cells using Accutase (Sigma) for fixation and immunostaining as described previously (2).…”
Section: Molecular Cloning Of Fgfrl1 and Shp-1 Fluorescent Proteinmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the high islet vascular density and the vascular phenotype, with a great number of fenestrations, is induced and maintained by secretion of vascular endothelial growth factor from the beta cells [9][10][11]. Recently, we and others have shown that endothelial cells signal back and contribute to maintenance [12], and during certain conditions even expansion, of the adult beta cell mass [6,[13][14][15]. In the present study, we tested the hypothesis that islet endothelial cell products may directly influence beta cell function.…”
Section: Introductionmentioning
confidence: 99%